Pendidikan Agama Islam dan Modernitas di Era 6.0 - Rosadi, Khumaini; Noorhaidi; Khojir (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
During the era of modernity 6.0, which is characterized by rapid technological advances and significant social changes, there are several challenges and opportunities for Islamic religious education. On the one hand, this era opens up new opportunities to spread religious values more widely and effectively through information and communication technology, but it also presents new challenges, such as individualism and the influence of secular culture which can weaken religious values. This abstract discusses the challenges and opportunities of Islamic religious education in the era of Modernity 6.0. Changes in people's lifestyles, a flood of information, fast-paced lifestyles, the influence of secular culture, and individualism are challenges, and opportunities are information and communication technology, online communities, globalization, and increasing religious awareness. Utilizing technology, creating interactive learning media, building online communities, improving teacher capabilities, strengthening family collaboration, changing lesson materials, improving interreligious communication, and increasing the role of religious institutions are some strategies for facing challenges and taking advantage of opportunities. In this abstract, it is found that Islamic religious education in the era of modernity 6.0 faces many challenges and opportunities. However, Islamic religious education can remain relevant and beneficial for the younger generation with appropriate and effective strategies.